Developing risk management framework for wellhead and christmas tree equipment - Abd Hamid, Abd Hamid (2019)
Poor design may cause product failure, can be affected the manufacturing processes such as delay in delivery time, increased cost, poor quality, lose time, and risk for lost time injury (LTI). To remain competitive in global marketplace the manufacturing wellhead and christmas tree equipment companies need to implement of risk management process, to analysis potential risk and failure. This thesis attempted to investigate an organization’s perception of risk management in manufacturing of wellhead and christmas tree equipment and determine the risk management culture that influence the implementation and practices of risk management. The main outcome of this research is to develop comprehensive risk management framework for effective risk management implementation in order to facilitate decision making. This is achieved through detailed review of relevant literatures, standard and survey technique and questionnaires through the research methodology process. The research procedure require collection of data which was obtained from the manufacturing and collection methods involve survey form, meeting with industrial experts and conduct pilot study to enable provision reaching some conclusions. There are 216 respondents from 13 companies in this research who completed and returned the survey form. The results obtained through testing of IBM SPSS statistic version 21 using data collected from industry showed the perception about risk management and implementation of the company in managing risk found that the mean value for the group variable company risk culture and implementation stage is moderate (slight lower 3 from likert scale 1-5) and Pearson correlation is positive and these are 3 factors of competency, motivation, knowledge and risk culture that influence toward implementation risk management successful. In conclusion, the above result satisfy the research aim of facilitating decision making process and the framework and flow diagram proposed in this thesis can be used for a guide to the practitioners and further study.